Biochemical markers in crop and forest species: a systematic review (Research, Society and Development, 2021)
Proteins and enzymes are informative biochemical markers frequently used in plant studies. The objective of this work was to present the studies with enzymes and proteins used as biochemical markers in crops and forest species—the articles prospected in the Scopus and Web of Science scientific databases in December 2020. The keywords were a combination of "agricultural" or "forest" with the Boolean operator and the enzymes' name: alcohol dehydrogenase/ADH, malate dehydrogenase/MDH, alpha-amylase/AMS, peroxiredoxin/PERX, and LEA proteins. Eighty-two articles addressed enzymes in agricultural or forest species were included in the analysis. The articles were published from 1976 to 2020, with an average annual publication of 12.2. Three hundred thirty-seven authors developed the annual percentage growth rate of 2.52% and articles. The most studied crops are Oryza sativa L., Glycine max L., Zea mays L., Hordeum vulgare L., specimens of the genera Triticum and Brassica. The forest species were Pinus, Picea, Nothofagus, Quercus, and Sorbus, and Fagus sylvatica L. The main tissues used for extraction are leaves, seeds, buds, and roots. The studies mainly deal with enzymes or proteins as markers associated with abiotic stresses and the structure or genetic diversity.